55.8k views
3 votes
Prove cos x / 1+sinx = tan ( π\4 - x/2)​

1 Answer

6 votes

Answer:


\displaystyle (\cos x)/(1 + \sin x) = \tan\left((\pi)/(4) - (x)/(2)\right).

Overview of the steps:

  • Apply the double-angle identity of sines and cosines to the left-hand side of the equation.
  • Apply the Pythagorean identity to the left-hand side of the equation.
  • Apply the angle sum and difference identity of sines and cosine to the right-hand side of the equation.

Explanation:

Double-angle identity of sines and cosines:


  • \cos (2\,\alpha) = \cos^2\alpha - \sin^2\alpha = (\cos\alpha + \sin\alpha)\, (\cos\alpha - \sin\alpha).

  • \sin(2\,\alpha) = 2\, \sin\alpha\, \cos\alpha.

Pythagorean identity for the sine and cosine of the same angle:


1 = \cos^2\alpha + \sin^2\alpha.

Angle sum and difference identity of sines and cosines:


\sin(\alpha - \beta) = \sin\alpha\, \cos\beta - \cos\alpha \, \sin\beta.


\cos(\alpha - \beta) = \cos\alpha\, \cos\beta + \sin\alpha \, \sin\beta.

Consider
x as the sum of two angles of size
(x/2). Start by applying the double-angle identity to the left-hand side.


\begin{aligned} \text{L.H.S.}&= (\cos(x))/(1 + \sin(x)) \\ &= (\cos^2(x / 2) - \sin^2(x / 2))/(1 + 2\, \sin(x / 2)\, \cos(x / 2))\end{aligned}.

Apply the Pythagorean identity to rewrite the "1" in the denominator as
\left(\cos^2(x / 2) + \sin^2(x / 2)\right).


\begin{aligned} \text{L.H.S.}&= (\cos(x))/(1 + \sin(x)) \\ &= (\cos^2(x / 2) - \sin^2(x / 2))/(1 + 2\, \sin(x / 2)\, \cos(x / 2))\\ &= (\cos^2(x / 2) - \sin^2(x / 2))/(\sin^2(x/2) + 2\,\sin(x/2)\, \cos(x/2) + \cos^2 (x/2))\end{aligned}.

Note that the denominator is now a perfect square. On the other hand, the numerator is in the form
(x^2 - y^2), which is equal to
(x + y)\, (x - y). Rewrite and simplify this expression:


\begin{aligned} \text{L.H.S.}&= (\cos(x))/(1 + \sin(x)) \\ &= (\cos^2(x / 2) - \sin^2(x / 2))/(1 + 2\, \sin(x / 2)\, \cos(x / 2))\\ &= (\cos^2(x / 2) - \sin^2(x / 2))/(\sin^2(x/2) + 2\,\sin(x/2)\, \cos(x/2) + \cos^2 (x/2)) \\[1em] &= ((\cos(x/2) + \sin(x/2))\, (\cos(x/2) - \sin(x/2)))/(\left(\sin(x/2) + \cos(x/2)\right)^2) \\ &= (\cos(x/2) - \sin(x/2))/(\sin(x/2) + \cos(x/2))\end{aligned}.

The tangent of an angle is equal to the ratio between its sine and its cosine. Apply the angle sum and difference identity of sine and cosine to the right-hand side.

Note, that the sine and cosine of
(\pi/4) are both equal to
\left(√(2)/2\right).


\begin{aligned}\text{R.H.S.} &= \tan\left((\pi)/(4) - (x)/(2)\right) \\ &= (\sin((\pi/4) - (x/2)))/(\cos((\pi/4) - (x/2)))\\ &= (\left(√(2)/2\right)\, \cos(x/2) - \left(√(2)/2\right)\, \sin(x/2))/(\left(√(2)/2\right)\, \cos(x/2) + \left(√(2)/2\right)\, \sin(x/2)) \\ &= (\cos(x/2) - \sin(x/2))/(\cos(x/2) + \sin(x/2))\end{aligned}.

Therefore:


\displaystyle \text{L.H.S.} = (\cos(x/2) - \sin(x/2))/(\sin(x/2) + \cos(x/2)) =\text{R.H.S.}.


\displaystyle (\cos x)/(1 + \sin x) = \tan\left((\pi)/(4) - (x)/(2)\right).

User Fazi
by
5.5k points